Psychophysical assessment of face perception deficits in adults with amblyopia through top-down and bottom-up visual processing pathways - Ming, Xiaolu; Huang, Gantian; Liao, Meng; Jiang, Ping; Liu, Longqian (Frontiers in Neuroscience, 2025)
PurposeThis study aims to investigate face perception ability in adult patients with amblyopia.MethodsWe conducted two psychophysical experiments. The Face-detection task involved 25 amblyopic patients and 25 healthy controls, using face stimulation at 6 stimulation intensities. The Toast task included 16 amblyopic patients and 15 healthy controls, with pure noise images and semantic cues designed to induce face perception. We recorded accuracy and reaction times (RT) and used the Kruskal-Wallis test with Wilcoxon comparisons to analyze group differences.ResultsIn the Face-detection task, amblyopic eyes (AE) exhibited significantly higher face detection thresholds than healthy controls (P < 0.05), indicating face detection deficit. AE showed lower accuracy at 20 and 67% stimulation intensities compared with HC and fellow eyes (Ps < 0.01). The Toast task revealed no significant differences in false alarm rate or RT were observed between groups (P > 0.1).ConclusionThis study shows that patients with amblyopia have impaired face perception, with higher threshold and lower accuracy, especially under lower stimulation conditions. These findings highlight the need for further research to understand the neural basis of these deficits and explore potential treatments. Ultimately, these study results may provide valuable insights and fill an important gap in the psychophysical understanding of amblyopia.